wecB Gene of Salmonella Gallinarum Plays a Critical Role in Systemic Infection of Fowl Typhoid - Ojima, Shinjiro; Ono, Hisaya K.; Okimoto, Ryo; Yu, Xiaoying; Sugiyama, Makoto; Yoshioka, Kazuki; Haneda, Takeshi; Okamura, Masashi; Hu, Dong-Liang (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Gallinarum (S. Gallinarum) is a host-specific pathogen causing severe systemic infection in poultry called fowl typhoid, which leads to substantial economic losses due to high morbidity and mortality in many developing countries. However, little is known about the pathogenic characteristics and mechanism of S. Gallinarum-induced systemic infection in chickens. In this study, we constructed a UDP-N-acetylglucosamine-1-phosphate transferase gene, which contributes to the biosynthesis of enterobacter common antigen (ECA), deletion mutant S. Gallinarum (wecB::Cm), and studied the pathogenic roles of ECA in the chicken model of systemic infection. The wecB::Cm mutant strain showed comparable growth but lower resistance to bile acid and nalidixic acid than the wild-type strain in vitro. In the oral infection model of chickens, the wecB::Cm strain was significantly attenuated in vivo. Chickens infected with wild-type strain showed typical clinical signs and pathological changes of fowl typhoid and died between 6 and 9 days post-infection, and the bacteria rapidly disseminated to systemic organs and increased in livers and spleens. In contrast, the wecB::Cm mutant strain did not cause chicken death, no significant clinical changes, and the bacterial numbers in the liver and spleen of the chickens were significantly lower than that of the chickens infected with the wild-type strain. In addition, the expressions of IL-1b, TNF-a and CXCLi1 in the livers of wecB::Cm-infected chickens were significantly lower than those of the chickens infected with the wild-type strain. Furthermore, the attenuated wecB::Cm strain could persistently colonize in the liver and spleen at low levels for up to 25 days post-infection and induce a protective immune response in the chickens. These results indicate that the wecB gene is an important virulence factor of S. Gallinarum in the chicken model of systemic infection, and a possibility of using the avirulence wecB::Cm mutant as a live attenuated vaccine strain for controlling fowl typhoid.